2005
DOI: 10.2355/isijinternational.45.1577
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Scale Investigation to Improve the Productivity of Stamp Charge Coke Oven through Optimisation of Bulk Density of Coal Cake

Abstract: In the recent past, it was realised that the gross coke yield was going down as a result of lower oven throughput in the stamp charged batteries of Tata Steel. The basic reason for this being the net reduction in the ash content of the coal blend used due to the incorporation of higher percentage of low ash imported coals and reduction in the ash content of captive coals through washing. The coals having higher ash content improves the bulk density, as the specific gravity of ash is higher than that of pure co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…The d 50 of the Waterberg sscc materials varied between 0.6 mm and 1 mm, whereas the crushing fineness was more than 99% < 3.25 mm. The particle sizes of the coals utilized in this study were similar to those suggested for compaction or stamping by various workers in the field, namely 85% to 99% < 3.25 mm (Dash et al, 2005;Kumar et al, 2008, Tiwari et al, 2012Madias and de Córdova, 2013;Rejdak and Wasielewski, 2015). In the case of the Oaky North sample, the d 50 was 0.7 mm with a crushing fineness of 95% < 3.25 mm.…”
Section: Particle Size Distributionsupporting
confidence: 81%
See 1 more Smart Citation
“…The d 50 of the Waterberg sscc materials varied between 0.6 mm and 1 mm, whereas the crushing fineness was more than 99% < 3.25 mm. The particle sizes of the coals utilized in this study were similar to those suggested for compaction or stamping by various workers in the field, namely 85% to 99% < 3.25 mm (Dash et al, 2005;Kumar et al, 2008, Tiwari et al, 2012Madias and de Córdova, 2013;Rejdak and Wasielewski, 2015). In the case of the Oaky North sample, the d 50 was 0.7 mm with a crushing fineness of 95% < 3.25 mm.…”
Section: Particle Size Distributionsupporting
confidence: 81%
“…The mineral components in coals are hydrophilic, and pure coal repels water, which in this case works against the cohesion of the blend. Hence, the lower the mineral content, the lower the bulk density of the coal cake, and this decreases the oven throughput (Dash et al, 2005). Less coalified coals contain more oxygen and hydrophilic functional groups than more coalified coals do.…”
Section: The Benefits Of An Increase In Coal Cake Bulk Density Includementioning
confidence: 99%
“…The minimum shear and compressive strength require for stable coal cake are around 14 709 N/m 2 and 156 906 N/ m 2 respectively. 19)…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in the E-v model, 16 assuming the relation between axial and lateral strains is hyperbolic, the tangential Poisson's ratio v t can be expressed as (2) where G, F and D are material constants given from the hyperbola through triaxial tests. Note that the sign of tensors in soil mechanics is contrary.…”
Section: Duncan-chang Constitutive Modelmentioning
confidence: 99%
“…Recently, research has focused mainly on the blending optimisation 1,[2][3][4] of raw material (coal powder) and on the factors affecting the density and strength of coal cake. [5][6][7] The stamping process itself is rarely studied so the lack of information on the stamping operation makes it difficult to analyse and optimise the design of the charging car and operational factors such as coal box pressure.…”
Section: Introductionmentioning
confidence: 99%